Analisis Upaya Preventif dalam KUHP terhadap Pertumbuhan Tindak Pidana Judi Online di Indonesia - agustina rahayu husein (Jurnal Hukum Lex Generalis, 2026)
The rapid growth of information technology has contributed to the increasing prevalence of online gambling crimes in Indonesia, as evidenced by the high volume of financial transactions and the growing number of users, resulting in significant social, economic and legal consequences. This study aims to analyze the preventive measures undertaken by law enforcement agencies to combat online gambling and to examine the challenges in implementing the 2023 Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) in supporting these preventive efforts. The research employs an empirical method with a socio-legal (juridicalsociological) approach. The findings indicate that existing preventive measures have not been implemented optimally. Furthermore, the 2023 Criminal Code remains predominantly repressive in nature and does not adequately regulate preventive mechanisms for addressing online gambling. Therefore, strengthening preventive legal regulations and enhancing inter-agency coordination are necessary to improve the effectiveness of online gambling prevention. These findings are expected to serve as a consideration in formulating more effective criminal law policies to prevent and tackle online gambling practices in Indonesia.